List of 31 New IRRI-NARES Varieties for India - Challa, Venkateshwarlu; Paul, Pronob J; Valenzuela, Myrtel; Bhosale, Sankalp; Sinha, Pallavi; Singh, Vikas Kumar (International Rice Research Institute, 2025)
Rice is a staple crop critical to India’s food security, yet its production is increasingly challenged by climate variability, water scarcity, and evolving consumer demands. In response, the International Rice Research Institute (IRRI), in collaboration with India’s National Agricultural Research and Extension System (NARES), has developed and released 31 high-performing rice varieties, officially notified in the Gazette of India in 2024, for large-scale cultivation across diverse rice-growing ecologies.